FAKTOR RISIKO TUBERKULOSIS PARU BTA POSITIF DAERAH DATARAN TINGGI KABUPATEN TEMANGGUNG PROVINSI JAWA TENGAH - , Susilawati; , dr.Iswanto, Sp.P, FCCP, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Tuberculosis (TB) became a public health problem in many countries around the world, including Indonesia. Indonesia ranks fourth with the highest TB burden in the world. TB case detection at Temanggung District is still below the national target, but subdistrict Tretep located which in the plateau Temanggung District, in the last 3 years showed an increasing trend of TB case finding (2008 (5%), (2009 (36%), 2010 (309 %)). For that we need research on risk factors house of tin-roofed, type of floor, extensive of ventilation, habits of open the windows, smoking habits, presence of household contacts to smear positive TB patients, because of problems at the sites of study and there is theory which the underlying that of the variable was to be a risk factor for the incidence of smear positive pulmonary TB. Methods: Type of study is analytic with case control design. Cases are TB patients of smear-positive a new type of age â¥ 15 years who have been diagnosed, undergoing treatment, was recorded in register TB-03 of Temanggung District since October 2010 - September 2011 , domiciled in the study area, total of 139 respondents. Controls are neighbors cases who are not diagnosed TB, total of 139 respondents with matching age and sex. Technique sampling of cases with a simple random sampling , whereas controls with purposive sampling. Analysis of data with univariate, bivariate (chi square), multivariate ( logistic regression backward stepwise method). Results:The results of the multivariate test, tin-roofed the house (OR 2.006, 95% CI 1.215 to 3.311, p-value 0.006), area ventilation <10% of floor area (OR 1.983, 95% CI 1.164 to 3.378, p-value 0.012), household contact with smear positive TB patients (OR 5.714, 95%g CI 2.375 to 13.745, p-value 0.000), as a risk factor for TB smear positive and statistically significant. Conclusion:The incidence of smear positive TB or likely to be at greater risk in people who live with smear positive TB patients, the house of tin-roofed, ventilation area <10% of floor area than people who do not live with smear positive TB patients, the house not of tin-roofed, ventilation area â¥10% of floor area on the plateau Temanggung district and statistically significant.